COVID-19 vaccination intention during early vaccine rollout in Canada: a nationwide online survey - Xuyang Tang; Hellen Gelband; Nico Nagelkerke; Isaac I. Bogoch; Patrick Brown; Ed Morawski; Teresa Lam; Prabhat Jha (Elsevier, 2021)
Background: Understanding vaccination intention during early vaccination rollout in Canada can help the government's efforts in vaccination education and outreach. Method: Panel members age 18 and over from the nationally representative Angus Reid Forum were invited to complete an online survey about their experience with COVID-19, including their intention to get vaccinated. Respondents were asked "When a vaccine against the coronavirus becomes available to you, will you get vaccinated or not?" Having no intention to vaccinate was defined as choosing "No - I will not get a coronavirus vaccination" as a response. Odds ratios and predicted probabilities are reported for no vaccine intentionality in demographic groups. Findings: 14,621 panel members completed the survey. Having no intention to vaccinate against COVID-19 is relatively low overall (9%) with substantial variation among demographic groups. Being a resident of Alberta (predicted probability = 15%; OR 0.58 [95%CI 0.14-2.24]), aged 40-59 (predicted probability = 12%; OR 0.87 [0.78-0.97]), identifying as a visible minority (predicted probability = 15%; OR 0.56 [0.37-0.84]), having some college level education or lower (predicted probability = 14%) and living in households of at least five members (predicted probability = 13%; OR 0.82 [0.76-0.88]) are related to lower vaccination intention. Interpretation: The study identifies population groups with greater and lesser intention to vaccinate in Canada. As the Canadian COVID-19 vaccination effort continues, policymakers may use this information to focus outreach, education, and other efforts on the latter groups, which also have had higher risks for contracting and dying from COVID-19. Funding: Pfizer Global Medical, Unity Health Foundation, Canadian COVID-19 Immunity Task Force.